Utilization of nanotechnology and experimental design in the development and optimization of a posaconazole‒calendula oil nanoemulgel for the treatment of mouth disorders - Alissa, Mohammed; Hjazi, Ahmed; Abusalim, Ghadah S.; Aloraini, Ghfren S.; Alghamdi, Suad A.; Alharthi, Nahed S.; Rizg, Waleed Y.; Hosny, Khaled M.; Binmadi, Nada (Frontiers in Pharmacology, 2024)
Essential oil-based nanoemulsions (NEs) are the subjects of extensive investigation due to their potential to address a variety of oral health issues. NEs are delivery systems that improve lipid medicine solubility and distribution to intended sites. The goal of the current study was to create and enhance a self-nanoemulsifying drug delivery paradigm based on calendula oil (CO) and decorated with chitosan (CS) that could deliver posaconazole (PSZ) for the treatment of gingivitis.Employing a response-surface Box-Behnken design, PSZ-CO-CS NEs were created with varying amounts of PSZ (10, 15, and 20 mg), percentages of CO (6%, 12%, and 18%), and percentages of CS (0.5%, 1.5%, and 2.5%). The optimized formulation resulted in a 22-mm bacterial growth suppression zone, 25-mm fungal growth inhibition zone, droplet sizes of 110 nm, and a viscosity of 750 centipoise (cP). Using the appropriate design, the ideal formulation was produced; it contained 20 mg of PSZ, 18% of CO, and 1.35% of CS. Furthermore, the optimal formulation had a more controlled drug release, larger inhibition zones of bacterial and fungal growth, and desirable rheologic properties. Additionally, the optimized formulation substantially lowered the ulcer index in rats when tested against other formulations. Thus, this investigation showed that PSZ-CO-CS NEs could provide efficient protection against microbially induced gingivitis.